1993
DOI: 10.1097/00003446-199306000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Brain Stem Responses to Air- and Bone-Conducted Clicks in the Audiological Assessment of At-Risk Infants

Abstract: Auditory brain stem responses [ABRs] to a i r and boneconducted clicks were used to assess the auditory status of 170 atirisk neonates. During the perinatal period, 20.6% [35/170 cases] of the at-risk infants failed ABRs to airconducted clicks at 30 dB nHL in a t least one ear. Earspecific results indicated an initial failure rate of 15.0% [51/340 ears]. Approximately twctthirds (32/51 ears] of these initial failures showed purely conductive deficits, whereas the remaining one-third [ I 9/51 ears] involved sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Consequently, their responses to bone-conduction ABR are dissimilar. Similar with the present study, Yang et al [10], found no prolonged latencies of wave V in infants in their survey.…”
Section: Discussionsupporting
confidence: 92%
“…Consequently, their responses to bone-conduction ABR are dissimilar. Similar with the present study, Yang et al [10], found no prolonged latencies of wave V in infants in their survey.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the CE-Chirp could prove to be effective for differential diagnosis of conductive and sensorineural hearing loss in newborns (cf. Yang et al, 1993) as ABRs were reliably recorded using both air-and bone-conducted signal deliveries.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained on the basis of the observation that with increasing intensity levels, there is shortening of the wave latencies due to the rapid fi ring and the quicker rising of synaptic potentials and, therefore, a decreased latency of transmission. It can be hypothesized that this increase in the fi ring rate with increasing intensities in compromised babies does not equal that of normal babies [11]. Hence, though the latencies may be comparable at lower intensities due to normal cochlear function, difference occurs at the higher intensities.…”
Section: Wave Imentioning
confidence: 95%